Optimal allocation of TCSCs by adaptive DE algorithm - Sakr, Walla S; El-Sehiemy, Ragab A; Azmy, Ahmed M (IET generation, transmission & distribution, 2016)
This study presents an adaptive differential evolution (DE) algorithm to allocate the thyristor-controlled series compensator (TCSC) incorporated with the reactive power management problem. In addition, a dynamic updating is applied for scaling and penalty factors to enhance the performance of the multi-objective DE algorithm. During the selection of the best candidate lines for efficient allocation of TCSC devices, three situations are considered for excluded transmission lines. These situations are the lines connected between two generating units; lines connected through transformers and the lines of low losses. The considered multi-objective function compromises between reducing power losses, improving voltage profile, reducing reactive power losses, reducing TCSC cost and reducing number of flexible alternating current transmission systems units. The optimal siting and sizing of TCSC is defined for normal and emergency operating conditions. The proposed procedure is employed for IEEE 9-bus and IEEE 30-bus test systems in addition to western delta network as a real part of the Egyptian network. Four case studies are considered for each test system to represent normal and abnormal operating conditions. Results clearly indicate the effectiveness of the adaptive DE algorithm to allocate perfectly the TCSC to enhance the system performance.